Satzstruktur und adverbiale Subordination. Eine Studie zum Deutschen und zum Italienischen - Blühdorn, Hardarik; Ravetto, Miriam (Linguistik Online, 2014)
This paper investigates the syntactic behaviour of adverbial clauses in contemporary German and Italian. It focuses on three main questions: (i) How many degrees of syntactic integration of adverbial clauses are there to be distinguished by an adequate grammatical description of the two languages? (ii) Which linear and hierarchical positions in the structure of the matrix sentence can be occupied by adverbial clauses? (iii) Which is the empirical distribution of adverbial clauses introduced by the conjunctions als, während, wenn, obwohl and weil in German, as well as quando, mentre, se, sebbene and perché in Italian? Responding to question (i), a distinction is drawn between strongly integrated, weakly integrated and syntactically disintegrated adverbial clauses. There are further degrees on the gradient of syntactic integration, which are not examined in this paper. Responding to question (ii), eight classes of structural positions in the matrix sentence are identified that can be occupied by adverbial clauses. Five of them are positions of syntactic integration, three are positions of disintegration. Responding to question (iii), the distribution of the ten classes of adverbial clauses is described on the basis of a corpus of internet data. Strongly integrated, weakly integrated and disintegrated adverbial clauses show clearly different distributions within the structure of the matrix sentence. Also the semantic classes of adverbial clauses (temporal, adversative, conditional, concessive, causal) are distributed differently.